2000
DOI: 10.1046/j.1365-2141.2000.01816.x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of mRNA for five species of cytochrome P450 in human bone marrow, bone marrow‐derived macrophages and human haemopoietic cell lines

Abstract: Summary. The expression of mRNA for ®ve cytochrome P450s (CYP1A1, 2A6/7, 2D6, 2E1 and 3A4) was studied in human bone marrow, bone-marrow-derived macrophages and blood monocyte-derived macrophages. Reverse transcriptase polymerase chain reaction (RT-PCR) detected expression of all ®ve CYPs in each of these cell populations. All ®ve CYPs were also expressed in the haemopoietic cell lines HL-60 and HEL and in Epstein±Barr virus (EBV)-transformed B-lymphoblastoid cell lines. The data suggest that bone marrow macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Although it was not evident whether a cytochrome P450 pathway could synthesize the metabolite EXP3179 in THP-1 macrophages, the expression of cytochrome P450 isoenzymes, 2C9 and 3A4, which are linked to losartan metabolism, is well defined in the lineage of monocytes/macrophages. 22,23 Alternatively, it was reported that losartan itself could serve as a PPARg agonist, 12 supporting the idea that losartan attenuates LPS-induced proinflammatory gene expression by acting as a PPARg agonist. In this study, we did not use other AT1R blockers with strong PPARg activity, such as telmisartan and irbesartan, or PPARg agonists, such as glitazone, to demonstrate the involvement of the PPARg pathway because we wanted to clarify the interaction between RAS and TLR-signaling pathways in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was not evident whether a cytochrome P450 pathway could synthesize the metabolite EXP3179 in THP-1 macrophages, the expression of cytochrome P450 isoenzymes, 2C9 and 3A4, which are linked to losartan metabolism, is well defined in the lineage of monocytes/macrophages. 22,23 Alternatively, it was reported that losartan itself could serve as a PPARg agonist, 12 supporting the idea that losartan attenuates LPS-induced proinflammatory gene expression by acting as a PPARg agonist. In this study, we did not use other AT1R blockers with strong PPARg activity, such as telmisartan and irbesartan, or PPARg agonists, such as glitazone, to demonstrate the involvement of the PPARg pathway because we wanted to clarify the interaction between RAS and TLR-signaling pathways in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of P450 2E1 in bone marrow has been implicated by Bernauer et al [15]. Hodges et al [13] found five P450s, including P450 1A1, 2A6/7, 2D6, 2E1, and 3A4 in bone marrow, in macrophages, and in hematopoietic cell lines. Nguyen et al [14] found even more P450 forms (16) in mononuclear fraction of peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…The information about expression of genes coding for biotransformation enzymes, especially P450s in population of CD34 + human hematopoietic stem and progenitor cells, is still limited. To date, expression of mRNA for five cytochrome P450s (CYP1A1, 2A6/7, 2D6, 2E1, and 3A4) was demonstrated in human bone marrow, in various types of macrophages, in cell lines HL-60 and HEL, and in Epstein-Barr virus-transformed B-lymphoblastoid cell lines as well as in mononuclear cells [13,14]. Presence of P450 2E1 in bone marrow cells was indicated by Western blotting [15].…”
Section: Cytochrome P450 In Stem Cellsmentioning
confidence: 99%
“…Consequently, the content of tissue-specific P450 isoforms may represent an important parameter determining both the therapeutic efficacy and susceptibility to the toxic effects of administered xenobiotics. In this regard, lymphatic tissue from spleen, thymus and bone marrow have been reported to express, albeit at considerably lower levels than observed in liver, isoforms from the CYP1A, CYP2A, CYP2B, CYP2E and/or CYP2J subfamilies [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%